#TITLE_ALTERNATIVE# - DWI JATMOKO (NIM : 10211067), KAMAL
Pr2Zr2O7 has a geometrically frustrated magnetic structure because of magnetic moment of the Pr3+ ions form tetrahedral lattices with another Pr3+ ions. In this report will discuss the state of phonons in room temperature of Pr2Zr2O7 with Raman Spectroscopy. Phonon state of three single crystal samples of Pr2Zr2O7 which grown with different condition are measured with and without polarization using Raman spectrometer Bruker Senterra with 785 nm wavelength laser and 50 mW power. Two out of three of the samples (sample 1 and 2) were grown in oxygen atmosphere and the rest was grown in argon atmosphere (sample 3). Wave number, intensity, and width of the peaks obtained will be analyzed using symmetry rules, based on measurements to assign vibration modes on phonons. All of the assignments have been done corresponding to symmetry rules on sample 1 and 2 i.e. A1g, Eg, and four T2g modes. On the other hand, the assignments of the sample 3 have been done only on Eg modes. From the unpolarized measurements in different points, sample 1 and sample 2 have higher homogeneity than sample 3. From the measurements of the polarized temperature dependent, peak 380 cm-1 showed a sharpening and intensity increasing at a temperature about 370 K - 400 K.